If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12b + -8 = 4 Reorder the terms: -8 + 12b = 4 Solving -8 + 12b = 4 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 12b = 4 + 8 Combine like terms: -8 + 8 = 0 0 + 12b = 4 + 8 12b = 4 + 8 Combine like terms: 4 + 8 = 12 12b = 12 Divide each side by '12'. b = 1 Simplifying b = 1
| 25x^2+15X-6=0 | | (-18)-(-39)= | | 8a-a=16 | | 5x-48=1x | | 4v-16=-9 | | (-27)-(-50)= | | x+x+3x=3 | | 1+6(2+3)= | | 0=-6w+30 | | (-9)-(9)= | | y+14=4 | | (25)-(8)= | | 3(2-3y)+5y=3y | | -[11x-(3x+5)]=-6-[4(3x-4)-2x] | | 3(2x+1)=2(1+3x)-1 | | b-5=0 | | 2=(x-40) | | (19)-(15)= | | (10)-(-30)= | | .2(x+.2)=24 | | -0.5y-7=-7.5 | | (2x+17)+13= | | (32)-(-19)= | | 3900=58x | | 2(x+1)+3(x+2)= | | (23)-(-4)= | | a-13a=6 | | (47)-(33)= | | 21-5x=7-7x | | (.66x+18)=(2x-5) | | 21-5x=7+7x | | (12)-(42)= |